Transnational trafficking networks of end-of-life vehicles and e-waste - Favarin, Serena (Global crime, 2023)
Based on case studies and interviews, it appears that the transnational trafficking of various waste types follows distinct paths. However, this information only provides a partial view of the global waste trafficking network, as it has never been studied by combining all the known illegal flows of different waste types. To address this gap, we analysed data from the Basel Convention National Reports to reconstruct networks of countries that engaged in illegal exchanges of end-of-life vehicles, e-waste, or both between 2016 and 2019. Our findings suggest that the structure of these networks and the countries involved in the trafficking vary depending on the waste type, with some similarities. While there are a few reciprocal ties, illegal end-of-life vehicles and e-waste typically move in one direction between countries. Most illegal flows occur from the Global North to the Global South, but trafficking also takes place within each of these regions.